Virus de la inmunodeficiencia felina (VIF): evaluación de las globulinas en pacientes infectados espontáneamente - Gómez, N. (2006)
Statistical correlation between parameters such as globulins, Alpha- Glycoprotein AGP, serum proteins fractions by electrophoresis and Toxoplasma gondii titles in cats infected with Feline Immunodeficiency Virus (FIV) were studied. Indirect Immunofluorecence titles to Toxoplasma gondii did not showed correlation with Total proteins and globulins. It was observed correlation between all types of proteins studied (r: 0,98, p<0,04). Total proteins versus globulins showed positive correlation (r:0,93, p <0,0001). Total protein versus alpha-globulin evidenced negative correlation (r:-0,75, p<0,01). AGP and alpha-globulins did not showed correlation and it was detected negative correlation with gamma-globulins (r:-0, 94, p<0,0001) and with globulins (r:-0,67, p<0,03). The patients evaluated showed a high level of Total proteins because of the increase of globulins. Gamma-Globulins were detected increased but there was not correlation with Toxoplasma gondii titles. It was not observed correlation between AGP and Alfa-globulins.